2022
DOI: 10.3390/ijerph192114235
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Impact of COVID-19 Lockdowns in Istanbul

Abstract: The World Health Organization (WHO) have set sustainability development goals to reduce diseases, deaths, and the environmental impact of cities due to air pollution. In Istanbul, although average pollutant concentrations have been on a downward trend in recent years, extreme values and their annual exceedance numbers are high based on the air quality standards of WHO and the EU. Due to COVID-19 lockdowns, statistically significant reductions in emissions were observed for short periods. However, how long the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Tomasz Turek et al [12] demonstrated that restricting anthropogenic activities did not have an impact on long-term changes and trends in air quality in Wroclaw, Poland. In contrast, Elçin Tan [13] found that the average air quality in Istanbul improved by about 17% during the long-term lockdown period (12 March 2020 to 30 June 2021). Overall, whether it is a short-term or long-term impact, the degree of change in air quality varied from region to region during COVID-19 [14,15].…”
Section: Introductionmentioning
confidence: 89%
“…Tomasz Turek et al [12] demonstrated that restricting anthropogenic activities did not have an impact on long-term changes and trends in air quality in Wroclaw, Poland. In contrast, Elçin Tan [13] found that the average air quality in Istanbul improved by about 17% during the long-term lockdown period (12 March 2020 to 30 June 2021). Overall, whether it is a short-term or long-term impact, the degree of change in air quality varied from region to region during COVID-19 [14,15].…”
Section: Introductionmentioning
confidence: 89%
“…While full restrictions were set on weekends, partial closure practices were carried out between 19:00 and 05:00 for fault in some periods and sometimes between 09:00PM and 05:00AM hours from the night (Tan, 2022 ).…”
Section: Introductionmentioning
confidence: 99%